Paths of democratic heresy: Catholics and Falangists in transit - José Rilla (Pasado y Memoria, 2020)
In Montevideo and in the context of Río de la Plata, Catholic Hispanism of the inter-war period had limited outcomes. However, it did have some impact on political and intellectual circles. The tendency underwent fascist and ’falangist’ drifts, which met greater obstacles to their deployment in the liberal Uruguay of the thirties than in Argentina, a country more open to Catholic nationalism. Two trips are taken here as references to capture the contradictory and disruptive alternatives: The one made by Jacques Maritain to Argentina and the one made by Carlos Real de Azúa to Spain. While the first, quite relevant for Latin America, opened up an anti fascist possibility in Catholic thinking, the second, on a notoriously smaller scale, displayed a variant of the Falangist disappointment that later sought after an arduous match with democracy.